Peringatan Hari Kemerdekaan Sebagai Upaya Penguatan Moderasi Beragama di Dusun Gupit - Erly Rizky Kamalia; Lailatun Nadipah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The promotion of religious moderation is crucial to be implemented in Dusun Gupit, considering the religious diversity among its residents, who consist of both Muslims and Buddhists. Following the "Religious Moderation Dialogue" held in the village, a follow-up activity titled the "August Competition with a Religious Moderation Theme" was organized as part of the 78th Independence Day celebration of the Republic of Indonesia. This event also aimed to reinforce the four pillars of Religious Moderation: national commitment, tolerance, rejection of violence, and the preservation of local wisdom. The activity adopted the Asset-Based Community Development (ABCD) approach, which emphasizes the strengths and potential within the local community. The implementation showed strong enthusiasm and positive reception from the residents, as evidenced by the absence of conflict or friction among participants throughout the event. The objectives were considered successfully achieved, marked by a high level of interfaith collaboration and solidarity. Moving forward, it is hoped that harmony among residents will continue to flourish, regardless of religious background, as a concrete manifestation of tolerance and a preventive measure against radicalism.